(untitled) (Bangladesh Journal of Pharmacology, 2016)
Epilepsy is an abnormality of nervous system showing seizures. Despite, the known antiepileptic activity of plants possessing antioxidant properties, Silybum marianum has not been studied yet. Therefore, present experiment was planned to evaluate antiepileptic potential of S. marianum (100, 200 and 300 mg/kg) seeds ethanol extract in pentylenetetrazol-induced kindled mice (n = 30). S. marianum seed extract (300 mg/kg) provided significant protection against pentylenetetrazol-induced convulsions (seizure intensity, latency and lethality) comparable with reference drug (valproic acid). Furthermore, 300 mg/kg/day dose was effective to prevent oxidative stress causing significant decrease in the lipid peroxidation (1.4 ± 0.4 nmol/mg protein) and increased superoxide dismutase (0.4 ± 0.1 µmol/mg protein) and catalase activity (4.7 ± 0.8 U/mL) of mice brain as compared to induced untreated group (p<0.05). It was concluded that antiepileptic activity of S. marianum seeds was due to its antioxidant property. Video Clip of Methodology: Experimental induction of seizures: 10 min 4 sec Click to watch